2022
DOI: 10.1109/jiot.2022.3177256
|View full text |Cite
|
Sign up to set email alerts
|

Bindi: Affective Internet of Things to Combat Gender-Based Violence

Abstract: The main research motivation of this paper is the fight against gender-based violence and achieving gender equality from a technological perspective. The solution proposed in this work goes beyond currently existing panic buttons, needing to be manually operated by the victims under difficult circumstances. Instead, Bindi, our end-to-end autonomous multimodal system, relies on artificial intelligence methods to automatically identify violent situations, based on detecting fear-related emotions, and trigger a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 76 publications
0
7
0
1
Order By: Relevance
“…As an example of the impact of GBV on women, the results of studies from 2000 to 2018 showed that more than one in four women (27%) between the ages of 15 and 49 had ever have had a sexual partner, experienced physical or sexual violence, or both, since the age of 15 [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an example of the impact of GBV on women, the results of studies from 2000 to 2018 showed that more than one in four women (27%) between the ages of 15 and 49 had ever have had a sexual partner, experienced physical or sexual violence, or both, since the age of 15 [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this work is to address the gender perspective methodology and not the design itself, so the device description is presented in [ 84 ] for further details.…”
Section: Use Case: Bindimentioning
confidence: 99%
“…Reconocer emociones a partir del habla, como el miedo o el estrés, causadas por situaciones de VBG, ha sido objeto de estudio con el fin de desarrollar dispositivos inteligentes capaces de detectar posibles casos de esta violencia. Por ejemplo, Binni es un sistema autónomo que combina el aprendizaje automático y el Internet de las cosas (IoT) para identificar y reportar automáticamente situaciones de riesgo de VBG (Miranda et al, 2022).…”
Section: Estado Del Arteunclassified